Caloric and Protein Infusion versus Dietary Prescription in Enteral Nutritional Therapy for Cancer Patients - Silva, Mikelly Joanny da (2021)
Introduction: Nutritional support for cancer patients is not restricted to the calculation of nutritional needs and dietary prescription, it is necessary that the prescribed volume is actually infused. Objective: To compare caloric and protein infusion with dietary prescription in cancer patients undergoing enteral nutritional therapy. Method: Retrospective, analytical study, conducted on nutritional monitoring cards who were hospitalized at least for seven days, exclusively under enteral nutritional therapy by tube or ostomy, between January 2009 and December 2012. The cards that met the selection criteria were ordered alphabetically and randomly selected by withdrawal interval (k=5). It was collected: age, sex, tumor location, nutritional composition, prescribed and infused volume of the enteral formula utilized. With these last two, the indicator “prescription versus infusion” was calculated. Student t test, paired t test and chi-square test were applied at a maximum significance level of 5%. Results: Of the 120 cards analyzed, men (61.7%) were more prevalent with mean age of 58.3±16.8 years. In 2010, higher means of the difference between prescribed and infused volume (-392.64 ml) and prescribed versus infused calories (-528.23 cal) were observed. Only 37.5% of the patients received a minimum of 70% of the prescribed volume. Conclusion: There was an inadequate intake of the infused in relation to the prescribed diet. It is suggested nutritional therapy interventions from the multi-professional team to minimize the complications encountered.